Pragmatics in the False-Belief Task: Let the Robot Ask the Question! - Baratgin, Jean; Dubois-Sage, Marion; Jacquet, Baptiste; Stilgenbauer, Jean-Louis; Jamet, Frank (Frontiers in Psychology, 2020)
The poor performances of typically developing children younger than 4 in the first-order false-belief task ``Maxi and the chocolate'' is analyzed from the perspective of conversational pragmatics. An ambiguous question asked by an adult experimenter (perceived as a teacher) can receive different interpretations based on a search for relevance, by which children according to their age attribute different intentions to the questioner, within the limits of their own meta-cognitive knowledge. The adult experimenter tells the child the following story of object-transfer: ``Maxi puts his chocolate into the green cupboard before going out to play. In his absence, his mother moves the chocolate from the green cupboard to the blue one.'' The child must then predict where Maxi will pick up the chocolate when he returns. To the child, the question from an adult (a knowledgeable person) may seem surprising and can be understood as a question of his own knowledge of the world, rather than on Maxi's mental representations. In our study, without any modification of the initial task, we disambiguate the context of the question by (1) replacing the adult experimenter with a humanoid robot presented as ``ignorant'' and ``slow'' but trying to learn and (2) placing the child in the role of a ``mentor'' (the knowledgeable person). Sixty-two typical children of 3 year-old completed the first-order false belief task ``Maxi and the chocolate'', either with a human or with a robot. Results revealed a significantly higher success rate in the robot condition than in the human condition. Thus young children seem to fail because of the pragmatic difficulty of the first-order task, which causes a difference of interpretation between the young child and the experimenter.